Pengaruh Zona Penempatan Berbeda pada Closed House terhadap Mikroklimatik Amonia, Ukuran Relatif Organ Limfoid, Kelenjar Tiroid, dan Usus Halus Ayam Broiler - Wahyu Fajar Arfianta; Teysar Adi Sarjana; Endang Widiastuti (Universitas Boyolali, 2020)
The purpose of this study was to determine the effect of different placement zones on closed houses on microclimatic ammonia, relative size of lymphoid organs, thyroid gland and small intestine of broiler chickens. The material used in the study was 360 broiler chickens taken from a population of 11000 with an initial body weight of 44.8 ± 1.66 grams. The design used was a randomized block design with 4 treatments and 6 groups so that there were 24 experimental units and 15 units each. The treatment given is T1 = 0 m from the inlet, T2 = 15 m from the inlet, T3 = 30 m inlet, T4 = 45 m from the inlet. The parameters observed were ammonia microclimatics in different zones, the weight of lymphoid organs, thyroid gland the length and weight of broiler small intestine. The results of the analysis of variance that has been done can be seen that changes in ammonia microclimatics in different placement zones had no significant effect (P> 0.05) on the relative size of broiler chicken lymphoid organs. The conclusion of this study is that the different placement zones in the closed house enclosure followed by ammonia microclimatic changes have not been able to influence the relative size of , the weight of lymphoid organs, thyroid gland the length and weight of broiler small intestine.